Lookup Table Technique by using Irradiation Intensity and Duty Cycle for Faster MPPT Application - Yuttikarn Lapkitticharoenchai; Anuwat Jangwanitlert (My University, 2023)
This research shows how Lookup Table technique can track MPP. This method uses calculation to find the exact value of duty cycle that make PV panel reach MPP. Therefore, its speed is faster than classical techniques especially P&O because knowing the exact value of duty cycle can make the controller control the switching device that makes PV reach MPP directly. Moreover, the swing at MPP is less P&O. However, the Lookup Table technique still be relied P&O to track MPP in the first period for automatically recording data into the Table for the Lookup Table technique. Hence, this method is going to be combined by both of P&O and Lookup Table. It is relied on the condition which technique is going to be operated. Lookup Table technique will be operated instead of P&O when the recorded data are enough and under defined the conditions that will be explain in this paper.
Keywords: Photovoltaic System Optimization Techniques; solar cell performance optimization; Advanced Battery Technologies Research